PEMANFAATAN QR CODE DALAM PENGEMBANGAN SISTEM INFORMASI KEHADIRAN SISWA BERBASIS WEB - Sri Murni; Raja Sabaruddin (Universitas Merdeka Malang, 2018)
The presence of students in the school is called by the term student presence. Understanding student presences contain two meanings, namely the problem of attendance and the absence of students in school. The presence and absence of students in school is closely related to student achievement. The conventional student attendance system can be developed into an application by utilizing QR Code technology. QR Code is the development of barcode (bar code) from one dimension into two dimensions. Where is much more practical and can convey information quickly with fast response. The method used in the development of attendance system is a waterfall that starts from the stage of analysis, design, coding, testing and support. While in the process of collecting data some of the methods undertaken are interviews, observation and literature study. The development of student attendance system into a web-based application is able to help and facilitate the teacher in recording attendance data of students, avoid fraudulent attendance process, improve data security and speed up student absenteeism.DOI: https://doi.org/10.26905/jtmi.v4i2.2144